2015
DOI: 10.1101/gad.268722.115
|View full text |Cite
|
Sign up to set email alerts
|

Ctr9, a key subunit of PAFc, affects global estrogen signaling and drives ERα-positive breast tumorigenesis

Abstract: The human RNA polymerase II (RNAPII)-associated factor complex (hPAFc) and its individual subunits have been implicated in human diseases, including cancer. However, its involvement in breast cancer awaits investigation. Using data mining and human breast cancer tissue microarrays, we found that Ctr9, the key scaffold subunit in hPAFc, is highly expressed in estrogen receptor α-positive (ERα + ) luminal breast cancer, and the high expression of Ctr9 correlates with poor prognosis. Knockdown of Ctr9 in ERα + br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 51 publications
10
46
0
Order By: Relevance
“…For instance, the human PAFc is required for the maintenance of embryonic stem cell identity [11], neuronal migration in mammalian brain [12], antiviral and pro-inflammatory response [13], and oncogenesis regulation [14, 15]. Our studies have demonstrated the involvement of Ctr9, a key scaffold subunit of human PAFc, in ERα-positive breast cancer progression and ERα target gene expression [16]. Specifically, using loss-of-function approach, we observed that depletion of Ctr9 led to apparent morphological change, decrease of proliferation, reduced colony formation, and impaired ERα-target gene expression in ERα-positive breast cancer cells [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the human PAFc is required for the maintenance of embryonic stem cell identity [11], neuronal migration in mammalian brain [12], antiviral and pro-inflammatory response [13], and oncogenesis regulation [14, 15]. Our studies have demonstrated the involvement of Ctr9, a key scaffold subunit of human PAFc, in ERα-positive breast cancer progression and ERα target gene expression [16]. Specifically, using loss-of-function approach, we observed that depletion of Ctr9 led to apparent morphological change, decrease of proliferation, reduced colony formation, and impaired ERα-target gene expression in ERα-positive breast cancer cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our studies have demonstrated the involvement of Ctr9, a key scaffold subunit of human PAFc, in ERα-positive breast cancer progression and ERα target gene expression [16]. Specifically, using loss-of-function approach, we observed that depletion of Ctr9 led to apparent morphological change, decrease of proliferation, reduced colony formation, and impaired ERα-target gene expression in ERα-positive breast cancer cells [16]. Moreover, Ctr9 regulates ERα protein stability and facilitates RNAPII recruitment and transcription-coupled histone modifications such as H2Bub1, H3K27ac, and H3K36me3 at the selected ERα targets [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inanition, several studies have suggested relations between Wnt or Notch signaling and different components of Paf1C [233][234][235][236]. Further, some of the Paf1C components e.g., Ctr9 are identified as a tumor suppressor factor in various organisms especially in human [232,[237][238][239][240][241].…”
Section: Mapping By Wgsmentioning
confidence: 99%
“…Additionally, studies in mammals showed that Ctr9 is necessary for early human development (implantation), and loss-of-function of hCtr9 results in the reduction of H3K36 trimethylation [223]. In addition, Ctr9 is identified as a tumor suppressor factor e.g., studies on human identified mutations in Ctr9 to be liable for Wilms tumor i.e., embryonal kidney cancer [238], and some types of breast cancer [241].…”
Section: Ctr9 a Key Components Of Paf1cmentioning
confidence: 99%